PENGEMBANGAN ASESMEN BERBASISKETERAMPILAN PROSES SAINS PADA MATERI LARUTAN PENYANGGA - Izu Khoirina Faiszatul Laili; Ratu Betta Rudibyani; Tasviri Efkar (Universitas Lampung, 2015)
The research use Borg asnd Galls RD method was conducted with the purpose to develop assessment base on science process skill on buffer solution topic and to describe the teachers and students responses about the developed assessment. Assessment was developed in the form of a written test question which it consist of 10 the multiple choice and 6 the description question. Base on validation result to developed assessment, it was obtained the percentage of readability, construction, and content suitability aspect were 83.08%; 83.16%; and 80%, respectively. Base on teachers responses to readability, construction, and content suitability aspect were 86.17%; 87.37%; and 83.33%. In other hand, student give responses to readability aspect equal to 85.7%. The trial results of the students' assessment showed that developed assessment was valid and reliability